The Economics of Banking - Matthews, Kent (Wiley, 2012)
The Economics of Banking describes and explains trends and operations in banking within an accessible microeconomic framework. It incorporates theory with the practical aspects of banking so as to set banking within the economics paradigm. A primary section on trends within banking leads on to chapters on the microeconomics of banking, market structure and regulation. The overall objective is to provide a mathematically accessible microeconomic context that will help students understand and analyze trends and operations in banking